Tailoring electrolyte to enable high-rate and super-stable Ni-rich NCM cathode materials for Li-ion batteries. (October 2021) - Cheng, Fangyuan; Zhang, Xiaoyu; Qiu, Yuegang; Zhang, Jinxu; Liu, Yi; Wei, Peng; Ou, Mingyang; Sun, Shixiong; Xu, Yue; Li, Qing; Fang, Chun; Han, Jiantao; et al.
Abstract: The detrimental effects on the electrochemical performances of high-capacity nickel-rich layered oxide cathode LiNi0.8 Co0.1 Mn0.1 O2 (Ni-rich NCM) are continuous irreversible phase transition, particle disintegration, and unstable cathode-electrolyte interface, which are usually induced by deleterious cathode-electrolyte reactions. Here, we report those side reactions are limited by a uniform inorganic/polymer cathode-electrolyte-interface (CEI) formed by in-situ electrochemical oxidation of a trace amount of dual additives in the traditional carbonate-based electrolytes. This CEI film not only eliminates the adverse cathode-electrolyte interface reaction and prevents the electrolyte penetration into the grain boundary but also hinders the formation of inactive rock-salt phase on the material surface. More significantly, it is demonstrated that this N, B, O-rich interface layer offers a fast Li + diffusion kinetic process to ensure a high-rate performance of the cathode, which is still a technical difficulty for the large application of Ni-rich NCM. Here, under the synergistic effect of dual additives containing lithium bis(oxalate)borate (LiBOB) and dopamine, the cell exhibits high-capacity retention over 92% after 200 cycles at 1 C, and also obtain a high specific capacity of 118 mA h g −1 at the high rate of 20 C. Building a stable and effect Li + -ion conductive interface film by optimizing the electrolyte formula is a facial and effective approach to develop aggressive high-capacity cathodes for high-energy storage applications. Graphical Abstract: A performance optimization mechanism induced by a uniform inorganic/polymer cathode-electrolyte-interface (CEI) formed by in-situ electrochemical oxidation of a trace amount of dual additives in the traditional carbonate-based electrolytes. Here, under the synergistic effect of dual additives containing lithium bis(oxalate)borate (LiBOB) and dopamine, the cell exhibits high capacity retention over 90% after 200 cycles at 1 C, and also obtain a high specific capacity of 118 mA h g −1 at the high rate of 20 C. ga1 Highlights: Side reactions are limited by a uniform inorganic/polymer cathode-electrolyte-interface formed by electrochemical oxidation. This N, B, O-rich interface layer hinders the formation of rock-salt phase on the cathode surface. The CEI film formed by in-situ polymerization offers a fast Li + diffusion kinetic process to ensure a high-rate performance.